Jakość jako determinanta konkurencyjności - studium przypadku - Szara, Katarzyna; Pierścieniak, Agata (Quality as a Determinant of Competitiveness - Case Study, 2006)
In the study an attempt is made to verify the connections resulting from introducing and functioning of quality management systems with their influence on the competitive position of firms. Quality actions, in case of analyzed enterprises, settle the aforementioned position. Consequently, there is: the increase of domestic and international market share, effective and efficient use of re- sources, appropriate relations between customers and the interested. As a result, it leads to the increase of customer's loyalty, assuming the individual employee's responsibility for firm moves, manufacturing wares in accordance with its own technology often with an original recipe and customer needs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 371-377